2003
DOI: 10.1002/chin.200301269
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Alterations in Cancer

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 1 publication
1
40
0
Order By: Relevance
“…27,28 Numerous reports have demonstrated that mtDNA is mutated and the mtDNA copy number is increased or decreased in human tumor tissues, depending on the specific tumor type. [29][30][31][32][33][34][35][36][37] A classic twin study estimated that the leukocyte mtDNA copy number has a heritability rate of 65%. 17 Several recent studies have indicated that the leukocyte mtDNA copy number is associated with altered cancer risks in a cancer type-specific manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Numerous reports have demonstrated that mtDNA is mutated and the mtDNA copy number is increased or decreased in human tumor tissues, depending on the specific tumor type. [29][30][31][32][33][34][35][36][37] A classic twin study estimated that the leukocyte mtDNA copy number has a heritability rate of 65%. 17 Several recent studies have indicated that the leukocyte mtDNA copy number is associated with altered cancer risks in a cancer type-specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…17 Several recent studies have indicated that the leukocyte mtDNA copy number is associated with altered cancer risks in a cancer type-specific manner. 17,22,38,39 In terms of GC, several studies have reported mtDNA mutation or depletion in tumor tissue 32,36,37 ; and, in a recent prospective study in a Chinese population, a significant association was observed between a low leukocyte mtDNA copy number and an increased risk of GC in blood drawn within 2 years before cancer diagnosis. 40 Hispanics are the largest nonwhite ethnic group in the United States and account for approximately 17% of the US population.…”
Section: Introductionmentioning
confidence: 99%
“…Malfunction of the respiratory chain subsequent to mtDNA mutations may in turn cause increased generation of ROS, leading to further DNA damage, genetic instability, and cancer progression (Pelicano et al, 2004;Singh, 2004). Indeed, increased mutations in mtDNA have been observed in cancer cells of various tissue origins (Wallace, 1999;Carew and Huang, 2002;Copeland et al, 2002;Nomoto et al, 2002;Carew et al, 2003). Since maintenance of mtDNA integrity is crucial to the normal functioning of the cell, and since mtDNA mutations are frequently observed in human cancers, a thorough understanding of the mechanisms by which cells maintain the stability of their mitochondrial genome is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mtDNA mutations have now been reported in cancer (1,16). mtDNA mutations could either arise in the female germ line and predispose to cancer (oncogenic germline mutations), or arise in the mtDNAs of the tissues (tumor-specific somatic mutations) and participate in the tumor progression process (17)(18)(19)(20)(21).…”
Section: Mitochondrial Dna Mutations In Cancermentioning
confidence: 99%
“…By virtue of the clonal nature of mitochondria and high copy number, mitochondrial mutations may provide a powerful molecular biomarker for the detection of cancer. It has been suggested that the extent of mitochondrial DNA (mtDNA) mutations might be useful in the prognosis of cancer outcome and ⁄ or the response to certain therapies (1).…”
mentioning
confidence: 99%